Elastic interaction in laminated beam glued-laminated bolted timber joints with circular bolt arrangements - Doppo Matsubara; Masaki Teranishi; Yoshiaki Wakashima (Journal of Wood Science)
Abstract In multiple-bolted joints of timber structures, the tightening of bolts induces elastic interaction, wherein the initial axial bolt force changes under the influence of deformation around adjacent bolts. In this study, tightening experiments and finite-element analysis (FEA) are conducted on a laminated beam-type glued-laminated bolted timber joint featuring eight bolts in a circular arrangement to investigate the influence of the tightening sequence on the axial force of each bolt. The results show that the bolt positions where the axial bolt force is significantly reduced due to elastic interaction differ between the counterclockwise and diagonal tightening sequences. For counterclockwise tightening, the most affected bolts are located at 135° and their diagonal counterparts relative to the center of the bolt arrangement. In this case, FEA indicates that the reduction in axial bolt force is caused by a decrease in the embedment stiffness of the washers into the wood, which in turn is due to the diagonal contact surface between the washers and the wood beneath adjacent bolts. For diagonal tightening, the most prominent reductions occur at 180° and their diagonal counterparts, which are attributed to a cumulative reduction in axial bolt force resulting from the sequential tightening of both adjacent bolts.